Unraveling the genetics of heat tolerance in chickpea landraces (Cicer arietinum L.) using genome-wide association studies - Danakumara, Thippeswamy; Kumar, Neeraj; Patil, Basavanagouda Siddanagouda; Kumar, Tapan; Bharadwaj, Chellapilla; Jain, Pradeep Kumar; Nimmy, Manduparambil Subramanian; Joshi, Nilesh; Parida, Swarup Kumar; Bindra, Shayla; Kole, Chittaranjan; Varshney, Rajeev K. (Frontiers in Plant Science, 2024)
Chickpea being an important grain legume crop, is often confronted with the adverse effects of hightemperatures at the reproductive stage of crop growth, drastically affecting yield and overall productivity. The current study deals with extensive evaluation of chickpea genotypes, focusing on the traits associated with yield and their response to heat stress. Notably, we observed significant variations for these traits under both normal and high-temperature conditions, forming a robust basis for genetic research and breeding initiatives. Furthermore, the study revealed, yield-related traits exhibited high heritability, suggesting their potential suitability for marker-assisted selection. SNP genotyping was carried by genotyping by sequencing (GBS) method for genome-wide association study (GWAS).Overall 27 marker trait associations (MTAs) linked to yield related traits among which five common MTAs displaying pleiotropic effects were identified after applying a stringent Bonferroni-corrected pvalue threshold of <0.05 (-log10(p) > 4.95) using BLINK model. Through an in-depth in silico analysis of these markers against the CDC Frontier v1 reference genome, we discovered that the majority of the SNPs were located at or in proximity to gene-coding regions. We further explored candidate genes situated near these MTAs, shedding light on the molecular mechanisms governing heat stress tolerance and yield enhancement in chickpea such as indole-3-acetic acid-amido synthetase GH3.1 with GH3 auxin-responsive promoter and Pentatricopeptide repeat-containing protein etc. The harvest index (HI) trait was associated with marker Ca3:37444451 encoding aspartic proteinase ortholog sequence of Oryza sativa subsp. japonica and Medicago truncatula known for contributing to heat stress tolerance. These identified MTAs and associated candidate genes may serve as valuable assets for breeding programs dedicated in tailoring chickpea varieties resilient to heat stress and climate change.